A self-assembled nanoparticle vaccine elicits effective neutralizing antibody response against EBV infection - Li, Ping; Jiang, Ziyi; Shi, Jingjing; Sha, Haochuan; Yu, Zihang; Zhao, Yan; Han, Sanyang; Ma, Lan (Frontiers in Immunology, 2025)
BackgroundEpstein–Barr virus (EBV) is a significant global public health concern because of its association with various malignancies and autoimmune diseases. Over 90% of the global population is chronically infected with EBV, impacting numerous cancer-related cases annually. However, none of the effective prophylactic vaccines against EBV is approved at present.MethodsIn this study, we developed a novel vaccine candidate based on epitope peptides from the receptor-binding domain of EBV-encoded gp350 glycoprotein to prevent EBV infection. These epitope peptides detected a binding capability with host cells were then fused by flexibility linkers and expressed in Escherichia coli to reduce the unnecessary glycan modifications to simulate their free-glycan status. The fused recombinant protein (L350) was displayed on the surface of ferritin-based nanoparticle. The immunogenicity of the L350–ferritin nanoparticle was evaluated in Balb/c mice, and the neutralizing titers of sera from immunized mice were detected by means of an infection blocking assay in an in vitro cell model.ResultsAll the five epitope peptides could bind to AKATA cells, and their fused recombinant protein (L350) was successfully presented on the surface of self-assembled ferritin nanoparticles. Sera from the L350–ferritin nanoparticle-immunized mice showed high titers of both L350 protein-specific and gp350D123 protein-specific antibodies, and sera from gp350D123 protein-immunized mice could also recognize L350 protein well. Most importantly, the L350–ferritin nanoparticle induced efficient neutralizing antibodies to block EBV-GFP infection in AKATA cells and also constructed a strong antigen-specific B-cell memory in immunized mice. Moreover, histopathological changes of main tissues from all vaccinated mice were not observed.ConclusionThese data indicate that the L350–ferritin nanoparticle vaccine candidate has considerable potential application in preventing EBV infection and provides a promising basis for developing prophylactic EBV vaccines.